Mathematical Programming Model on Joint and Recovery of Paper Scrap - Zhixia JIANG; Haifeng LUO; Jianjun YANG; Zhengqiang WEN (Institute of Advanced Engineering and Science, 2014)
The joint and recovery of paper scrap was an optimal matching issue. The automatic restoration technology for the broken document was designed according to different cutting ways of the paper shredder. As the fragment data was an one-side print file, a nonlinear programming model with no constraint conditions was established for the straight-cutting broken paper scrap from a given print file of the same page, and the nonlinear programming model with restraint programming model was established for the broken scrap with straight cut and cross cut. For the paper scrap data from a one-page print file in English printed on both sides, the joint was accomplished by the ant colony algorithm.